The effect of using some of the exercises Albleomterc in the development of muscular power of the two men and their impact in improving the performance of the skill bulwark of the game volleyball - Kadhim, Sami; Abdul alsamie, Himy (Journal of Physical Education, 2008)
Volleyball is considered one of the modern sports compared to other sports. Yet it spread quickly. The aim of the research is to identify the important of Plyometrics on the development of muscular power and the improvement of the level of performing Block. The researchers used the experimental method. The subjects were (30) forth year college students of the department of Teaching. The subjects were divided into two equal groups. The researcher concluded that using some plyometric exercises significantly improved blocking as shown from pre and post tests of the experimental group. The results of post tests showed significant improvement in long jump, throwing the medicine ball and Blocking from position (3).